Development of Applications for Simplification of Boolean Functions using Quine-McCluskey Method - Eko Dwi Nugroho (Telematika, 2021)
Purpose: This research makes an application to simplify the Boolean function using Quine-McCluskey, because length of the Boolean function complicates the digital circuit, so that it can be simplified by finding other functions that are equivalent and more efficient, making digital circuits easier, and less cost.Design/methodology/approach: The canonical form is Sum-of-Product/Product-of-Sum and is in the form of a file, while the output is in the form of a raw and in the form of a file. Applications can receive the same minterm/maksterm input and do not have to be sequential. The method has been applied by Idempoten, Petrick, Selection Sort, and classification, so that simplification is maximized.Findings/result: As a result, the application can simplify more optimally than previous studies, can receive the same minterm/maksterm input, Product-of-Sum canonical form, and has been verified by simplifying and calculating manually.Originality/value/state of the art: Research that applies the petrick method to applications combined with being able to receive the same minterm/maksterm input has never been done before. The calculation is only up to the intermediate stage of the Quine-McCluskey method or has not been able to receive the same minterm/maksterm input.